Geographic Information System Mapping of Location Distribution Homestay Area Waingapu City Sumba Web-Based East Sumba - Jeti, Estherlita Grace Bulu; Talakua, Alfrian Carmen; Uly, Hawu Yogia Pradana (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
Based on the results of the identification of the needs of tourists looking for lodging in the city of Waingapu, there is a lack of spatial information (latitude and longitude), non-spatial (owner's name, price, facilities, address, contact) with the nearest route. Although available on google maps, it is still lacking because it is still incorporated with hotels, boarding houses and other housing. Therefore, a Web-based Geographic Information System for Mapping the Distribution of Homestay Locations in the Waingapu City Area of East Sumba is made to provide recommendations to tourists who need lodging in accessing Homestayinformation by determining the user's location point and the nearest Homestay will appear. Maps will direct to the location of the selected lodging house accompanied by the desired information. This system was built using the PHP programming language with the MySQL Database. The method used in this research is the Waterfall model for system development and Euclidean Distance for the calculation of the closest distance.